1995
DOI: 10.1152/ajpendo.1995.268.1.e60
|View full text |Cite
|
Sign up to set email alerts
|

In vivo insulin mimetic effects of pV compounds: role for tissue targeting in determining potency

Abstract: Peroxovanadium (pV) compounds activate the insulin receptor kinase in hepatocytes and inhibit the dephosphorylation of insulin receptors in hepatic endosomes with highly correlated potencies (Posner, B. I., R. Faure, J. W. Burgess, A. P. Bevan, D. Lachance, G. Zhang-Sun, J. B. Ng, D. A. Hall, B. S. Lum, and A. Shaver J. Biol. Chem. 269: 4596-4604, 1994). After intravenous administration, K2[VO(O2)2(picolinato)].2H2O [bpV(pic)], VO(O2) (picolinato) (H2O)2 [mpV(pic)], K[VO(O2)2(picolinato)].3H2O [bpV(phen)], and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…We hypothesized that transient incubation of neonatal mouse ovaries in vitro with bpV(pic), a PTEN inhibitor (7)(8)(9), allows the activation of dormant follicles. Ovaries containing mainly primordial follicles were obtained from neonatal mice at day 3 of age.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that transient incubation of neonatal mouse ovaries in vitro with bpV(pic), a PTEN inhibitor (7)(8)(9), allows the activation of dormant follicles. Ovaries containing mainly primordial follicles were obtained from neonatal mice at day 3 of age.…”
Section: Resultsmentioning
confidence: 99%
“…In view of this, experiments were done to determine whether bpV(phen) (21) could modulate the course of the infection in a murine leishmaniasis model (32). Infection by L. major, the causative agent of cutaneous leishmaniasis, was inhibited by 60% (p Ͻ 0.05) in bpV(phen)-treated BALB/c mice (Fig.…”
Section: Attenuation Of Mø and Other Host Immune Functions Bymentioning
confidence: 99%
“…19). It was demonstrated that a number of chemically defined pV derivatives, each containing an oxo ligand, one or two peroxo anions in the inner coordination sphere of vanadium, and an ancillary ligand, were equally potent PTP inhibitors stable in aqueous solution (20) that can activate the insulin receptor kinase and mimic insulin biological action in vivo (21). Moreover, they have the capacity to inhibit the proliferation of nervous cell lines in vitro (22) and activate the response of immune cells (23).…”
mentioning
confidence: 99%
“…1A) provides the opportunity to more fully characterize the action of peroxovanadium within the cell. The action of vanadium can also be modified by organic ligands that facilitate cellular targeting and biochemical specificity (20,21); for example, we found that BMOV (Fig. 1B) induced apoptosis in B cell lineages but enhanced the activation of T cell lineages (15).…”
mentioning
confidence: 97%